A wall base ventilation system applied at different wall vgeometries-numerical simulation of the evaporative process - J. M. P. Q. Delgado (2012)
This work describes the moisture transfer process between a moving air flux and a saturated cylindrical pillar, in alignment with the direction of flow. Numerical solution of the partial differential equation describing moisture conservation gave the concentration field near the saturated surface and the mass transfer flux was integrated to give values of the Sherwood number as a function of the relevant parameters. An expression is proposed that accurately describes the dependence found numerically between the value of the Sherwood number and the values of Peclet number and aspect ratio, L/d(1), of the cylindrical pillar in contact with a wall base ventilation system, the Humivent device. For large enough cylinder diameter, the problem degenerates into mass transfer from a planar surface and the same equation applies, with L/d(1) = 0. The importance of the equation was demonstrated through the application of a practical example, namely, in the drying process of a porous media.